Aplikasi Berbasis Java Netbeans Untuk Meningkatkan Hasil Penjualan Usaha Kain Batik Pada Rumah Batik Danar Hadi - Andri Andri; Adhis Darussalam Pamungkas (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of research is to make it easier to manage the sales data of the Rumah Batik Danar Hadi store so that it becomes more effective and efficient as it can help slove the job problems related to the management of sales data. The research method used in the analysis and design of Java Netbeans-based sales system is a qualitative descriptive that is with direct observation, and also conduct interviews with related parties to get the information needed. In addition, researches also conduct research with literature methods based on references and various discussion as well as from various media that contain the necessary information. Analyze needs, design, implementation and coding, and testing. The result of this research is a computerized system that Can facilitate the work of Rumah Batik Danar Hadi in the collection of incoming batik, sold batik, employee data, and buyer data, up to sales reports that can be printed every month or every day. There is also a member card for customers who want to get special discounts for members only. This can draw the buyer's attention to a regular customer at the store.